Contribution of urban green areas to the environmental quality of the district of Comas- Lima, year 2011 - Malca C., Nora (2012)
The investigation showed that the management of urban green areas related to environmental quality and pollution control , and management assessed the municipal district of Comas to 2011, from the perspective of the population for this survey was applied to 449 people . It showed that 80 % believe that the management of green areas is related to environmental quality, only 40 % felt that they contribute to pollution control. It was concluded that the population is aware of the importance of green areas in urban dynamics , but not all the benefits that these provide . It is recommended to implement an effective program of tree seedlings , shrubs , and train personnel responsible and educate people on this issue.